Inclusão de alunos com transtorno do espectro autista no ensino e aprendizagem da matemática: um estudo de caso em dois municípios da Amazônia paraense - NEGRÃO, Adrielli Miranda Silva (2022)
The objective of this work is to understand how the process of inclusion of students with autism spectrum disorder in the teaching and learning of mathematics occurs in schools in the municipality of Santa Isabel do Pará and APAE in the municipality of Tomé-Açu/PA. School inclusion is one of the dimensions of social inclusion that can only be achieved by promoting access to quality education, as well as other fundamental rights. The methodological design presented in this article is the result of an exploratory research project with field description and recording of observations made through a field diary. In the course of the research, difficulties were encountered in the production of information, such as: number of students with ASD in all analyzed institutions, and the level of autism of these students. However, the topic is intriguing due to the unknowns surrounding its causes. There are several gaps to be explored in relation to ASD, but the most significant are the gaps in the preparation of educators to serve these students and promote their integral development.